Impaired emotional autobiographical memory associated with right amygdalar-hippocampal atrophy in Alzheimer’s disease patients - Philippi, Nathalie; Botzung, Anne; Noblet, Vincent; Rousseau, François; Després, Olivier; Cretin, Benjamin; Kremer, Stéphane; Blanc, Frédéric; Manning, Liliann (Frontiers in Aging Neuroscience, 2015)
We studied the influence of emotions on autobiographical memory (AbM) in patients with Alzheimer’s disease (AD), characteristically triggering atrophy in the hippocampus and the amygdala, two crucial structures sustaining memory and emotional processing. Our first aim was to analyze the influence of emotion on AbM in AD patients, on both the proportion and the specificity of emotional memories. Additionally, we sought to determine the relationship of emotional AbM to amygdalar-hippocampal volumes. Eighteen prodromal to mild AD patients and 18 age-matched healthy controls were included. We obtained 30 autobiographical memories per participant using the modified Crovitz test (MCT). Analyses were performed on global scores, rates and specificity scores of the emotional vs. neutral categories of memories. Amygdalar-hippocampal volumes were extracted from 3D T1-weighted MRI scans and tested for correlations with behavioral data. Overall, AD patients displayed a deficit in emotional AbMs as they elicited less emotional memories than the controls, however, the specificity of those memories was preserved. The deficit likely implied retrieval or storage as it was extended in time and without reminiscence bump effect. Global scores and rates of emotional memories, but not the specificity scores, were correlated to right amygdalar and hippocampal volumes, indicating that atrophy in these structures has a central role in the deficit observed. Conversely, emotional memories were more specific than neutral memories in both groups, reflecting an enhancement effect of emotion that could be supported by other brain regions that are spared during the early stages of the disease.